A Comparison of Safety and Effectiveness Between Wingspan and Neuroform Stents in Patients With Middle Cerebral Artery Stenosis - Zhou, Kai; Cao, Yuan; He, Xiao-Hui; Qiu, Zhong-Ming; Liu, Shuai; Gong, Zi-Li; Shuai, Jie; Yang, Qing-Wu (Frontiers in Neurology, 2021)
Background: Percutaneous transluminal angioplasty and stenting with the Wingspan stent has proven safe and effective in patients with middle cerebral artery stenosis (MCAS), but the off-label use of the Neuroform stent might be an alternative treatment. This study aimed to compare the safety and effectiveness of the above two intracranial stents in patients with MCAS. Methods: We retrospectively analyzed consecutive patients with symptomatic MCAS who had been treated with the Neuroform EZ or the Wingspan stent. A propensity score was generated to control for differences in baseline characteristics. The endpoints were the rate of peri-procedural complications within 30 days after stenting, the in-stent restenosis rate, and any target-vessel-related stroke or deaths during follow-up. Results: After matching for propensity score, the peri-procedural complication rate in the Wingspan group was 7.4% compared with 5.6% in the Neuroform group (p = 1.00), while the follow-up in-stent restenosis rates were 23.3 vs. 14.3%, respectively (p = 0.41). In the restenosis group, the patients tended to be younger (p < 0.01) and the degree of artery stenosis before stenting was higher (p ＜ 0.01). Conclusion: This study indicated that in patients with symptomatic MCAS, Neuroform EZ stents are an alternative to Wingspan. Moreover, younger age and higher degree of artery stenosis before stenting might be a risk factor of in-stent restenosis.